Suicidal Ideation, Psychological Distress and Child-To-Parent Violence: A Gender Analysis - Martínez-Ferrer, Belén; Romero-Abrio, Ana; León-Moreno, Celeste; Villarreal-González, María Elena; Musitu-Ferrer, Daniel (Frontiers in Psychology, 2020)
Child-to-parent violence is a growing public health problem with consequences for perpetrators and families. Most research has focused on individual and family risk factors. However, little is known about its links with individual outcomes. The aim of this study was to analyze the relationships between CPV and psychological distress, suicidal ideation and self-concept in school-aged adolescents, taking into account the gender perspective. A study was conducted with a sample of 8,115 adolescents, aged between 11 and 16 years (M = 13.34; SD = 1.04) from the State of Nuevo León, Mexico. A MANOVA 3x2 was performed to analyze the data. The results showed that adolescents involved in CPV showed higher levels of psychological distress and suicidal ideation and lower levels of family and social self-concept. It was also observed that girls with higher levels of CPV also reported the lowest levels of psychological distress and suicidal ideation, as well as the lowest levels of family self-concept. The findings highlight that adolescents and especially girls involved in CPV also report internal maladjustment outcomes. Finally, the results and their implications for research and intervention with adolescents involved in CPV are discussed.